AB0773 Health care utilization in dutch systemic sclerosis patients. (23rd January 2014) - Meijs, J.; Zirkzee, E.; Schouffoer, A.; Henquet, S.; Caljouw, M.; Stijnen, T.; Huizinga, T.; Schuerwegh, A.; Vliet-Vlieland, T.
Abstract : Background: Given the complexity of the Systemic Sclerosis (SSc), patients usually require multidisciplinary treatment involving, apart from the rheumatologist, other medical specialists and non-medical health professionals such as physical therapists, occupational therapists, dieticians, nurses or psychologists (1 -3 ). Research on the extent of health care utilization among SSc patients is scarce, therefore is a lack of information about which kind of patients are at risk having a high health care utilization, especially in Europe. Objectives: To examine health care utilization and its determinants among patients with SSc. Methods: A cross-sectional survey among all patients with SSc visiting an outpatient clinic of an academic hospital in the Netherlands was done. Assessments included socio-demographic characteristics, the Short Form-36 (SF-36) and the Scleroderma Health Assessment Questionnaire (SHAQ). In addition, a survey on health care utilization was administered, including a registration of contacts with health care services since onset of disease, contacts and number of visits with health care services over the last 12 months. A total health care utilization score of all visits in the last 12 months was computed and classified as high care utilization and low care utilization according to the median. Logistic regression analysis was used to determine the relationship between high and low health care utilization as dependent variable and socio-demographic and disease characteristics as independent variables. Results: 64 patients returned the questionnaires (83% response rate). Their mean age was 55 years and 55% of the patients were female. Over the last 12 months 83% of the patients had had contact with one or more physicians. On average, patients reported 3.9 visits (SD 2.9) to a rheumatologist and 6.9 visits (SD 9.3) to other medical specialists over the last 12 months. 61% of patients had had contact with one or more health professionals in the last 12 months, with the physiotherapist being most frequently mentioned. The median total health care utilization was 6 visits over the last 12 months. The univariate logistic regression analysis showed that higher SHAQ total score, low PCS scores and autoantibodies were significantly associated with high health care utilization. Multivariate regression showed that only a higher SHAQ score was significantly associated with higher health care utilization. Conclusions: Patients with SSc visited a considerable number of various health care providers. Patients with more functional disability were using more health care. References: Bernatsky S, Panopolis P, Hudson M Pope J, LeClercq S, Robinson R, et al. Demographic and clinical factors associated with physician services use in systemic sclerosis. J Rheumatol 2009;36:96-98. Johnson SR, Carette S, Dunne J v. Scleroderma: Health services utilization from patients' perspective. J Rheumatol 2006;33:1123-7. Schouffoer AA, Zirkzee EJM, Henquet SM, Caljouw MAA, Steup-Beekman GM, Laar JM v, et al. Needs and preferences regarding health care delivery as perceived by patients with systemic sclerosis. Clin Rheumatol 2011; 30:815-824. Disclosure of Interest: J. Meijs Grant/research support from: an unrestricted educational grant of Actelion Pharmaceuticals Nederland BV (Woerden, The Netherlands)., E. Zirkzee: None Declared, A. Schouffoer: None Declared, S. Henquet: None Declared, M. Caljouw: None Declared, T. Stijnen: None Declared, T. Huizinga: None Declared, A. Schuerwegh: None Declared, T. Vliet-Vlieland Grant/research support from: non-profit foundation National Reumafonds (Stichting Nationaal Reumafonds)